2010
DOI: 10.5830/cvja-2010-024
|View full text |Cite
|
Sign up to set email alerts
|

Coping and metabolic syndrome indicators in urban black South African men

Abstract: SummaryUrbanisation is associated with obesity, hypertension and development of the metabolic syndrome (MS). We aimed to assess the use of different coping styles and their influence on increases in MS indicators and target end-organ damage (TOD) in urban black African men. A sample of 53 men was classified as clear high active (AC, n = 30) or passive coping (PC, n = 23) responders, using the Amirkhan African validated coping style indicator. Blood pressure (BP) was recorded with an aneroid sphygmomanometer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Considering sex differences; African men in the low cortisol category have a ten times higher risk of increased ACR, than those in the high cortisol category. This confirms results from previous studies, where African men revealed attenuated cortisol responses associated with structural wall remodelling [32] and poorer health than their female and Caucasian counterparts [2,13,32,42]. From these results, it is evident that African men with low or possible down-regulated cortisol levels reveal more vulnerability for renovascular disease than their high cortisol as well as Caucasian counterparts.…”
Section: Low Cortisol and Renal Impairmentsupporting
confidence: 89%
“…Considering sex differences; African men in the low cortisol category have a ten times higher risk of increased ACR, than those in the high cortisol category. This confirms results from previous studies, where African men revealed attenuated cortisol responses associated with structural wall remodelling [32] and poorer health than their female and Caucasian counterparts [2,13,32,42]. From these results, it is evident that African men with low or possible down-regulated cortisol levels reveal more vulnerability for renovascular disease than their high cortisol as well as Caucasian counterparts.…”
Section: Low Cortisol and Renal Impairmentsupporting
confidence: 89%
“…Sub‐Saharan Africans experience a high prevalence of cardiovascular disease (Gaillard, ). These findings are supported by the synergistic effect of the metabolic syndrome and defensive active coping responses in urban African men (Du Plessis, Malan, & Malan, ; Malan, Malan, Wissing, & Seedat, ).…”
mentioning
confidence: 74%
“…The physiological profile of urban AC African males resembled a vascular α‐adrenergic profile or loss of control, which is more commonly reflective of PC responses (Hamer & Malan, ). An apparent dissociation between β‐adrenergic behavioral and physiological cardiometabolic AC responses was thus demonstrated in urban African males (Du Plessis et al., ; Malan et al., ). Such dissociation may lead to wear and tear on the body (allostatic load) and an increased cardiometabolic disease risk (McEwen, ).…”
mentioning
confidence: 99%
“…These risk factors may be coping strategies that are utilised when living in an urban environment, 11,20 and have been associated with increased WC, 21 and subsequently with the progression of MetS.…”
Section: Menmentioning
confidence: 99%
“…10 MetS can contribute to the strain of microalbuminuria as a marker of target organ damage. 8,9,[11][12][13][14] It has been found that various MetS risk factors have been associated with renal impairment with regard to target organ damage in the SABPA population. 8,15 Determining ethnic-, gender-, and age-specific waist circumference cut-off points to predict metabolic syndrome: the Sympathetic Activity and Ambulatory Blood Pressure in Africans (SABPA) study JEMDSA The aim of this study was firstly to develop a WC cutoff point for Africans and Caucasians in ethnic-, gender-and age-specific groups (25-45 years and 46-65 years) for MetS in this cohort.…”
Section: Introductionmentioning
confidence: 99%